Relativistic equation-of-motion coupled-cluster method: application to closed-shell atomic systems - Pathak, Himadri; Sahoo, B. K.; Das, B. P.; Vaval, Nayana; Pal, Sourav (Physical Review Applied, 2014)
We report our successful implementation of the relativistic equation-of-motion coupled-cluster (EOMCC) method. This method is employed to compute the principal ionization potentials (IPs) of closed-shell rare-gas atoms, He-like ions, Be-like ions, along with Na+, Al+, K+, Be, andMg. Four-component Dirac spinors are used in the calculations, and the one-and two-electron integrals are evaluated using the Dirac-Coulomb Hamiltonian. Our results are in excellent agreement with available measurements, which are taken from the National Institute of Science and Technology database. The accuracies of the calculations are estimated to be within one half of a percent for He-like and Be-like ions and 1% for the heavier systems. We also present results using the second-order many-body perturbation theory and random-phase approximation in the EOMCC framework. These results are compared with those of EOMCC at the level of single and double excitations in order to assess the role of the electron correlation effects in the intermediate schemes considered in our calculations.

Relativistic equation-of-motion coupled-cluster method for the double-ionization potentials of closed-shell atoms - Pathak, Himadri; Ghosh, Aryya; Sahoo, B. K.; Das, B. P.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2014)

Relativistic equation-of-motion coupled-cluster method for the ionization problem: application to molecules - Pathak, Himadri; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2014)
We report the implementation of the four-component spinor relativistic equation-of-motion (EOM) coupled-cluster method within the single- and double-excitation approximation to calculate the ionization potential of molecules. We have applied this method to calculate vertical ionization potentials of the molecules XH (X = F, Cl, Br, I) along with Cl-2 and Br-2 in their closed-shell configuration. We have also presented intermediate results using the second-order many-body perturbation-theory level in the EOM framework to understand the role of electron correlation. All the calculated values are compared with the available experimental results. Our results are found to be in good agreement with sophisticated experiments, and relative deviation of less than 1% is achieved for all the considered systems.

Relativistic equation-of-motion coupled-cluster investigation of the trends of single and double ionization potentials in the He and Be isoelectronic systems - Pathak, Himadri; Sahoo, B. K.; Sengupta, Turbasu; Das, B. P.; Vaval, Nayana; Pal, Sourav (Journal of Physics B-Atomic Molecular and Optical Physics, 2015)
We employ a four-component spinor relativistic equation-of-motion coupled-cluster (EOMCC) method within the single-and double-excitation approximation to calculate the single ionization potentials (IPs) and double ionization potentials (DIPs) of the He and Be isoelectronic sequences up to Ne. The obtained results are compared with the available results from the National Institute of Standards and Technology (NIST) database to test the performance of the EOMCC method. We also present intermediate results at different levels of approximations in the EOMCC framework to gain insight of the effect of electron correlation. Furthermore, we investigate the dependence of the IPs and DIPs of these ions on the ionic charge and observe that these follow parabolic trends. Similarities between the trends of IPs and DIPs in both the classes of considered systems are categorically demonstrated.
Keywords: coupled-cluster method; double ionization potentials; equation-of-motion theory

Relativistic extended coupled cluster method for magnetic hyperfine structure constant - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2015)

Relativistic coupled-cluster study of RaF as a candidate for the parity- and time-reversal-violating interaction - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2016)
We have employed both the Z-vector method and the expectation-value approach in the relativistic coupled-cluster framework to calculate the scalar-pseudoscalar (S-PS) P, T-odd interaction constant W-s and the effective electric field E-eff experienced by the unpaired electron in the ground electronic state of RaF. Further, the magnetic hyperfine structure constants of Ra-223 in RaF and Ra-223(+) are also calculated and compared with the experimental values wherever available to judge the extent of the accuracy obtained with the employed methods. The outcome of our study reveals that the Z-vector method is superior to the expectation-value approach in terms of accuracy obtained for the calculation of ground-state property. The Z-vector calculation shows that RaF has a high Eeff (52.5 GV/cm) and W-s (141.2 kHz), which makes it a potential candidate for the electric dipole moment of the electron (eEDM) experiment. An estimation of uncertainty associated with our final results is made, and it is found that it lies below 10%.

Relativistic equation-of-motion coupled-cluster method for the electron attachment problem - Pathak, Himadri; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Computational and Theoretical Chemistry, 2016)
The article considers the successful implementation of relativistic equation-of-motion coupled cluster method for the electron attachment problem (EA-EOMCC) at the level of single- and double- excitation approximation. The implemented relativistic EA-EOMCC method is employed to calculate ionization potential values of alkali metal atoms (Li, Na, K, Rb, Cs, Fr) and the vertical electron affinity values of LiX (X = H, F, Cl, Br), NaY (Y = H, F, Cl) starting from their closed-shell configuration. Both four component and exact two-component calculations are done for all the opted systems. Further, we have shown the effect of spin-orbit interaction considering the atomic systems. The results of our atomic calculations are compared with the values from the NIST database and the results are found to be very accurate (<1%). (C) 2015 Elsevier B.V. All rights reserved.

Relativistic double-ionization equation-of-motion coupled-cluster method: application to low-lying doubly ionized states - Pathak, Himadri; Sasmal, Sudip; Talukdar, Kaushik; Nayak, Malaya K.; Veval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2020)
This article deals with the extension of the relativistic double-ionization equation-of-motion coupled-cluster (DI-EOMCC) method [H. Pathak et al. Phys. Rev. A 90, 010501(R) (2014)] for the molecular systems. The Dirac-Coulomb Hamiltonian with four-component spinors is considered to take care of the relativistic effects. The implemented method is employed to compute a few low-lying doubly ionized states of noble gas atoms (Ar, Kr, Xe, and Rn) and Cl-2, Br-2, HBr, and HI. Additionally, we presented results with two intermediate schemes in the four-component relativistic DI-EOMCC framework to understand the role of electron correlation. The computed double ionization spectra for the atomic systems are compared with the values from the non-relativistic DI-EOMCC method with spin-orbit coupling [Z. Wang et al. J. Chem. Phys. 142, 144109 (2015)] and the values from the National Institute of Science and Technology (NIST) database. Our atomic results are found to be in good agreement with the NIST values. Furthermore, the obtained results for the molecular systems agree well with the available experimental values.